Exploring the Relationship Between Academicians via Reference Parsing - Cay, Gizem; Mungen, Ahmet Anil; Dogan, Emre; Kaya, Mehmet (Ieee, 2019)
Although the citation number is significant for a paper, it is important to determine the value of citation with the information of the citations' owner and their value for revealing the value of the citations. Our study proposes a method for parsing the reference sections of an academic publications. It will provide a graphical representation of the relationships of the people who give and cite the resulting shredding works in a weighted directional graph. Sobiad Citation Index and TUBITAK Dergipark and ULAKBIM TRDizin were used as the data set. The proposed method was found to be successful and result show in the graphs and experimental results.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 21-22, 2019 -- Inonu Univ, Malatya, TURKEY
Keywords: academic publication; reference parsing; bibliographic analysis